Pengaruh Bauran Pemasaran 7P Terhadap Kepuasan dan Loyalitas Konsumen Ledug Coffee Indonesia - Nuzuliyani, Dyah Firdausi; Winarno, Sri Tjondro; Rizkiyah, Noor (Universitas Medan Area, 2025)
Marketing mix plays an important role in today's business world, because consumer satisfaction and loyalty are created from a good marketing mix strategy. This study aims to analyze the effect of the 7P marketing mix consisting of product, price, place, promotion, people, process and physical evidence on consumer satisfaction and loyalty of Ledug Coffee Indonesia ground coffee. The population in this study were consumers who had purchased and consumed ground coffee products from Ledug Coffee Indonesia with a sampling technique using purposive sampling and data obtained by distributing questionnaires to 74 respondents. The method used in this study is the evaluation of the SEM model using Partial Least Square (PLS). The results of this study indicate that the 7P marketing mix has a positive relationship with consumer satisfaction. The product, price and process variables have a positive and significant effect on satisfaction, while the place, promotion, people and physical evidence variables do not have a significant effect on consumer satisfaction of Ledug Coffee Indonesia. Consumer satisfaction has a positive and significant effect on consumer loyalty. Consumer satisfaction of Ledug Coffee Indonesia is influenced by several indicators, the most important of which is coffee quality